Characterisation of Klebsiella pneumoniae Xylanase and Increment of Its Activity in Heterologous Expression System - Hussain, Mohd Hasnain; Zainol, Suhaila; Ming Chong, Nikson Fatt-; Awang Husaini, Awang Ahmad Sallehin (Borneo Journal of Resource Science and Technology, 2016)
A xylanase DNA sequence with a total length of 642 bp was previously isolated from a xylanolytic Klebsiella pneumoniae. Xylanase gene primers were designed with the addition of BamH1 and EcoR1 restriction enzyme sites in order get a full xylanase gene that is in-frame with pSTAG expression vector. The isolated xylanase gene was amplified using the designed primers through PCR, then cloned and expressed in E. coli BL21 (DE3). In-silico characterization showed that the recombinant xylanase has a molecular weight of 23.9 kDa and a pI of 9.32. The signal peptide cleavage site for the recombinant xylanase was predicted to be between residues 61 and 62. The activity of the crude recombinant xylanase was 2.015 U/mL, which was higher than the crude native xylanase activity, with maximum at 0.642 U/mL. Staining of the birchwood xylan agar plate with Congo red showed a clearing zone around E. coli BL21 (DE3) colonies with recombinant pSTAG plasmid even without being induced with IPTG. This implied leaky expression of the E. coli BL21 (DE3) secretion system, which recognized the signal sequence of the recombinant xylanase, and proceeded to cleave and secreted out the mature protein into the culture medium. MALDI-TOF analysis of a 20 kDa protein present in the culture medium confirmed that the recombinant xylanase had been secreted into the culture medium.